The emotional profile of Slovak freshmen in teaching English as a foreign language - Kralova, Zdena; Petrovic, Frantisek; Hrbackova, Karla; Sebokova, Jessica (Frontiers in Psychology, 2024)
The article focuses on tracing changes in Slovak pre-service TEFL student teachers' emotional states over the first semester of their university study and detecting possible factors inciting their emotions. It highlights the importance of understanding these emotional states as they significantly impact students' perceptions of their suitability as educators. A mixed-methods approach was employed to collect qualitative and quantitative data through questionnaires, reflections, and interviews. The sample consisted of 67 non-native Slovak first-year TEFL students. It was found that the students experienced a range of emotions, from initial confusion and worry to eventual joy and contentment. Negative emotions were mainly triggered by the flood of new information and study-related factors, while positive emotions were associated with the supportive attitude of teachers and the freedom of university life.